Palaeobiology of early carboniferous fishes and contemporary lacustrine biota of the Waaipoort Formation (Witteberg Group), South Africa - Evans, F. J.(Fiona Jocelyn) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.